PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP FEE AUDITOR EKSTERNAL - Yulika Wahyu Adi Pratama; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the influence of good corporate governance mechanism with external auditor fees on all companies listed on Bursa Efek Indonesa (BEI) during 2009-2013. Good corporate governance mechanisms in this study consisted of the independent commissioners, the board of commissioners, the board of commissioner meetings, audit committee, audit committee meetings and internal auditor. Collecting data is using purposive sampling method to all companies listed in Bursa Efek Indonesia (BEI) during 2009-2013. A total of 76 companies were utilised as sample in this research. Before being conducted the regression test, it is examined by using the classical assumption tests. This study uses multiple linear regression model as the analysis instrument. It was shown that the number of independent commisioners, the size from board of commissioners, the size of audit committee, and internal auditor have a significant influence with external auditor fees. However, the meeting of the board commissioners and the meeting of audit committee do not have significant influence with external auditor fees.